Investigation of Cyber Crime in the Indonesian Legal Framework - Rusman, Rusman; Kamaludin, Ahmad (Journal La Sociale, 2024)
Cybercrime in Indonesia is influenced by complex factors such as technological advancement, anonymity, lack of security awareness, inequality of technological development, financial reasons, and low law enforcement capacity. The legal regulation of cybercrime is based on the current legal sources both in the Criminal Code and laws outside the Criminal Code. Some categories of cybercrime cases handled in the Electronic Information and Transaction Law include illegal contents, illegal access, illegal interception, data leakage and espionage, system interference, misuse of devices, and data interference. Cybercrime is a criminal offence that uses computers and the internet as a means. Legal reform in handling cybercrime must be carried out with a policy approach that contains value considerations. Criminal law reform in overcoming information technology crimes must be oriented towards a value approach. Cybercrime is a crime that uses computers or computer networks as the main tool. In Indonesia, there is no specific legal definition for cybercrime. Cybercrime can be in the form of unauthorised access, illegal contents, data leakage, trojan horses, and others.